Boron-nitrogen-phosphorous doped graphene nanoplatelets for enhanced electrocatalytic activity. (February 2018) - Routh, Parimal; Shin, Sun-Hee; Jung, Sun-Min; Choi, Hyun-Jung; Jeon, In-Yup; Baek, Jong-Beom
Graphical abstract: Boron (B)-nitrogen (N)-phosphorus (P) doped GnPs (BNP-GnPs) were synthesized by Poly(anilineboronic acid, PABA), which is one of the conducting polymers and acts as a feedstock for BNP doping, was in-situ grafted to edge-amine functionalized GnPs (A-GnPs). After heat-treatment, the resultant BNP-GnPs demonstrated significantly improved electrocatalytic activity towards the oxygen reduction reaction, suggesting that the BNP-GnPs can be one of the best alternatives to precious Pt-based electrocatalysts. Highlights: Boron (B)-nitrogen (N)-phosphorus (P) doped graphene nanoplatelets (GnPs) were prepared. BNP-GnPs were realized by edge-grafting of poly(anilineboronic acid, PABA) and subsequent annealing. The structure of BNP-GnPs was confirmed by spectroscopic and microscopic analyses. The BNP-GnPs demonstrated significantly improved electrocatalytic activity towards the oxygen reduction reaction. BNP-GnPs can be one of the best alternatives to precious Pt-based electrocatalysts. Abstract: Doping with foreign atoms is a powerful technique for modifying the inherent properties of a host materials. In this work, we report a strategy for preparing multiple heteroatom-doped graphene nanoplatelets (GnPs). Poly(anilineboronic acid, PABA), which is one of the conducting polymers, was in-situ grafted to edge-amine functionalized GnPs (A-GnPs) in phosphoric acid. The isolated PABA grafted A-GnPs phosphoric acid salts (PA-GnP salts) were heat-treated at 900 °C under argon atmosphere to yield boron (B)-nitrogen (N)-phosphorus (P) doped GnPs (BNP-GnPs). The structure of the BNP-GnPs was confirmed by various techniques, including transmission electron microscopy, scanning electronic microscopy, X-ray photoelectron spectroscopy, Raman spectroscopy and thermogravimetric analysis. The BNP-GnPs demonstrated significantly improved electrocatalytic activity towards the oxygen reduction reaction, suggesting that BNP-GnPs can be one of the best alternatives to precious Pt-based electrocatalysts.